1996
DOI: 10.1002/pro.5560051208
|View full text |Cite
|
Sign up to set email alerts
|

A distant evolutionary relationship between bacterial sphingomyelinase and mammalian DNase I

Abstract: The three-dimensional structure of bacterial sphingomyelinase (SMase) was predicted using a protein fold recognition method; the search of a library of known structures showed that the SMase sequence is highly compatible with the mammalian DNase I structure, which suggested that SMase adopts a structure similar to that of DNase I. The amino acid sequence alignment based on the prediction revealed that, despite the lack of overall sequence similarity (less than 10% identity), those residues of DNase I that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…Based on this prediction and supporting experimental evidence (4,22,23) the function of several residues in the B. cereus enzyme have been suggested. is not carried out by a His in a similar position in the mammalian sequence but by a residue unique to eukaryotic enzymes (7).…”
Section: Sequence Alignments Of Eukaryotic Enzymes With Bacterial Nsmsupporting
confidence: 57%
See 3 more Smart Citations
“…Based on this prediction and supporting experimental evidence (4,22,23) the function of several residues in the B. cereus enzyme have been suggested. is not carried out by a His in a similar position in the mammalian sequence but by a residue unique to eukaryotic enzymes (7).…”
Section: Sequence Alignments Of Eukaryotic Enzymes With Bacterial Nsmsupporting
confidence: 57%
“…Subsequent site-directed mutagenesis ( Table II) has shown that mutations His136Ala and His272Ala at positions corresponding to general base and acid in other phosphodiesterases, resulted in a great reduction of the enzyme activity consistent with their proposed function. Mutational analysis of the corresponding residues in bacterial NSM and DNAse I had a similar impact on activity of these enzymes (4). It has also been reported (10) that the His272Asn mutation in the human enzyme resulted in a loss of NSM activity, as determined in transiently transfected HEK 293 cells.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…1). It had previously been noted that the AP-endonucleases share sequence similarity with the endonuclease domain of long interspersed nuclear element-1 (LINE-1 or L1) retrotransposons and sphingomyelinases (36,37). A more recent sequence analysis identified the conservation of fold and catalytic residues between the Mg 2ϩ -dependent endonucleases and a variety of signaling proteins including the inositol polyphosphate 5-phosphatases and the yeast carbon catabolite repressor protein Ccr4p (38).…”
Section: -Phosphatases and Ap Base Excision Repair Endonucleases 37057mentioning
confidence: 99%